Is Genome Editing Unnatural? Nature in Bioethics, the Politics of Bioethics, and the Political Dimension of Nature - Odzuck, Eva (Genome Editing. Between Moral Hazard and Legal Uncertainty., 2018)
The concept of nature and naturalness plays an important role in academic and public bioethical discussions. Given the obvious weakness of arguments that are based on a genetic and/or totalizing view of nature, the immense and repeated efforts to criticize them demand explanation. The repeated critique of such weak arguments and the tendency to avoid the category of nature can be explained (at least in part) by political motivations. While an unjustified appeal to nature, or a description of genome editing as unnatural, is of course problematic, we cannot develop the contours of a responsible genome policy without the dimension of nature. I work with the hypothesis that our relation to nature is in itself deeply normative and political, and conclude that a responsible biopolicy requires us to bring the question of nature back into the center of our political philosophy and our liberal democracie
Keywords: Genome Editing; Political Theory; Nature; Democracy; Liberalism; Bioethics